Implied Volatility Modelling with Neural Network-Corrected Parametric Models and Arbitrage-Free Constraints - Tapio, Alvar (My University, 2025)
This thesis examines implied volatility modelling through a hybrid framework that combines traditional parametric models with neural network corrections and an arbitrage-free adjustment step. Classical models such as Black-Scholes provide analytical convenience but are unable to capture the nonlinear dynamics observed in real-world. Recent studies highlight the potential of neural networks to improve predictive accuracy, though these approaches often lack explicit mechanisms to guarantee arbitrage-free outcomes. To address this, the study integrates feedforward neural networks with parametric baselines and subsequently applies the Stochastic Volatility Inspired (SVI) method to enforce structural consistency. Using SPY option data, the analysis evaluates both same-day interpolation, and short-term forecasts over horizons of one, five, and twenty-one trading days. Results indicate that neural network-corrected models deliver superior predictive performance compared to standard benchmarks, while the SVI post-processing effectively removes arbitrage opportunities without sacrificing accuracy. The findings demonstrate the value of combining theoretical structure with data-driven flexibility, offering contributions to both academic research and practical option market applications.

Tämä tutkielma tarkastelee implisiittisen volatiliteetin mallintamista hybridikehikon avulla, joka yhdistää perinteiset parametristen mallien ennusteet, neuroverkkokorjaukset sekä arbitraasivapaan sopeutusvaiheen. Klassiset mallit, kuten Black-Scholes, tarjoavat analyyttista selkeyttä, mutta eivät kykene kuvaamaan reaalimaailmassa havaittuja epälineaarisia dynamiikkoja. Viimeaikaiset tutkimukset osoittavat, että neuroverkot voivat parantaa ennustetarkkuutta, mutta niistä usein puuttuvat eksplisiittiset mekanismit, jotka varmistavat arbitraasittomuuden. Tätä ongelmaa ratkaistaan tässä työssä yhdistämällä Feed Forward-neuroverkot parametristen optiomallien kanssa ja soveltamalla tämän jälkeen Stochastic Volatility Inspired (SVI) -menetelmää rakenteellisen johdon- mukaisuuden varmistamiseksi. Empiirisessä analyysissa käytetään SPY-optiodataa, ja arviointi kohdistuu sekä saman päivän interpolaatioon että lyhyen aikavälin ennusteisiin yhdelle, viidelle ja kahdellekymmenelleyhdelle kaupankäyntipäivälle. Tulokset osoittavat, että neuroverkkokorjatut mallit tuottavat tarkempia ennusteita kuin perinteiset vertailumallit, ja että SVI-jälkikäsittely poistaa arbitraasimahdollisuudet heikentämättä ennustetarkkuutta. Havainnot korostavat teoreettisen rakenteen ja dataohjautuvan joustavuuden yhdistämisen arvoa, tarjoten uusia näkökulmia sekä akateemiseen tutkimukseen että käytännön optiomarkkinoiden sovelluksiin.